Regulation on the Implementation of Halal Product Assurance in Indonesia: Statute Approaches Study - Aziz, Muhammad; Ghofur, Abdul; Hidayati, Niswatin Nurul (Universitas Islam Sultan Agung, 2021)
This research was focused on the regulation of halal product assurance implementation in Indonesia on statute approaches study and the crucial issues associated with it. In the context of providing halal product assurance implementation, regulation is the basis of legality for all elements of the state in organizing the State. Before the emergence of the Halal Product assurance (JPH) Law, there were many regulations relating to the assurance of halal products. In forming a regulation, there are crucial issues/topics that suck up a lot of public attention, so that it can influence a policy that will be ratified. The conclusions of this research included; first, there were several crucial issues and topics related to the implementation of halal product assurance in Indonesia, they were; (1) halal certification/labeling; (2) mandatory (obligation) or voluntary in halal certification; (3) criminal provisions; and (4) halal product assurance management institutions. Second, halal product assurance regulations when viewed from the Statute Approach can be analyzed using three legal principles, consisting of (1) the principle of Lex Superior Derogat Legi Inferiori concluded that all halal product assurance rules that have a high position must replace all lower halal product assurance rules. (2) The principle of Lex Specialis Derogat Legi Generali confirmed that the Halal Product Assurance (JPH) Law was a specific regulation governing the assurance of halal products. This Halal Product assurance (JPH) Law replaced the previous halal product assurance rules; and (3) the principle of Lex Posterior Derogat Legi Priori required that the halal product assurance provisions contained in the Halal Product assurance (JPH) Law replaced the existing halal product assurance rules in the previous period.